Tradisi Menerbeb Pada Suku Pakpak Sebagai Penghormatan Pada Orang Tua Melalui Pendekatan Pada Efesus 6:1-3 - Andika M.A Padang; Nipa I.I Waruwu; Heppi Manik; Siska Tumangger; Eli Boi Sinamo (Jurnal Magistra, 2024)
This research is a written work whose truth is found and seeks the truth behind a tradition in the Pakpak tribe. From the results of this research, the author searched from various sources to reveal the importance of the menerbeb tradition in the Pakpak tribe. As time goes by, times are developing and new discoveries are being made, so slowly this tradition becomes forgotten and is rarely done by anyone as a sign of respect. Through this article, the author reveals the purpose, meaning and biblical basis of the menerbeb tradition of the Pakpak tribe. This article will also aim to explain how important it is to preserve the traditions that exist in the tribes of each region and to maintain traditional values ​​through traditions that have been passed down by ancient ancestors.